Relativistic electron bunch excitation of wake fields in magnеtoactive plasma - Balakirev, V.A.; Karas, V.I.; Karas, I.V.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2000)
We have been demonstrated that a multiple excess of the accelerated bunch energy εmax over the energy of the exciting. REB is possible in a magnetoactive plasma at a certain relationship between the parameters of the “plasmabunch-magnetic field” system owing to a hybrid volume-surface character of REB-excited wake fields, even without using the REBs contoured in the longitudinal direction.